Akulturasi Budaya dalam Desain Kemasan “Alingbao Bakpao Kekinian“ - Amanda Cindy Aisyah; Fauzan Aulia (Lembaga Pengembangan Kinerja Dosen, 2024)
Alingbao is a food and beverage business in the city of Padang. The concept of cultural acculturation combines the traditional food of a race, namely Minangkabau and Chinese. This design aims to optimize the function and structure of Alingbao packaging, maximize the shape and visuals of the packaging so that information and brand awareness of the product is conveyed to consumers and potential consumers. This design uses the 4D method which consists of Define, Design, Develop and Disseminate with the development results in the form of pop-ups. The analysis method used is SWOT analysis (strengths, weaknesses, opportunities, threats). The main media in this design are three packages consisting of primary and secondary packaging. The supporting media for this design are social media, menu price lists, cups, hanging banners, aprons and tape. The main and supporting media in the design have also gone through a feasibility test in the form of a prototype. Meanwhile, the feasibility test indicators themselves consist of packaging layout, packaging visual elements, structure, function and packaging materials. This aims to ensure that the packaging is suitable and suitable for use.